سياسة الاستثمار في الجزائر - أفاق وتحديات – - زينات, أسماء (جامعة الوادي - University of Eloued, 2017)
Thanks to the Recent Economic Transformations in the World, and the growing pace of Globalization it is necessary for Algeria to strengthen the capacity of the national economy in Order to achieve the gradual integration with the global economy, economic policy through structural reforms ; economic measures and actions; and legal and social contributes to creating a stimulating environment for investment whether local or foreign. It also allows these actions to highlight Investment opportunities and benefits available, and within this framework it may Since the early 1990s Algeria worked on restructuring its economy in line with the Transformations that have occurred in the international arena.Algeria began with the legislative decree 93-12 of 5 May 1993 on the promotion of investment.During the beginning of the Millennium ,Algeria creates a set of administrative structures designed to support the development of investment projects under 01-03 dated 20 August 2001 on investment development. Despite efforts devoted to promote and encourage both local and Foreign Investment, However the Investment recorded in the country did not correspond to the expectations and level the enormous investment opportunities that are available on Algeria.
The policy of investment in Algeria -Prospects and Challenges
مقال
Keywords: الاستثمار، التنمية الاقتصادية، الاستثمار في الجزائر; Investment, economic development, investment in Algeria.